Properties of quenched and self-tempered reinforcing steel subjected to high temperature and different cooling conditions. (7th May 2021) - Hager, Izabela; Kańka, Stanisław; Maślak, Mariusz
Abstract : Purpose: The study presents test results concerning the impact of high temperature and different cooling conditions on the mechanical properties of quenched and self-tempered reinforcing steel. The purpose of this paper is to clarify the extent of the history of the material's temperature development profile, the course and the intensity of fire exposure and how cooling conditions determines its properties. Design/methodology/approach: Each specimen series was heated to the temperatures of T = 200°C, 400°C, 600°C, 700°C, 800°C and 1, 000 °C. The specimens were either slowly cooled down or subjected to rapid cooling with water quenching, which can be encountered during a firefighting operation. Additionally, stress–strain relationships, microhardness and structural observations were also performed. Findings: The results of the presented experiments have shown that the steel bars previously heated in fire conditions were very sensitive to the cooling intensity. The test results from the steel specimens – that were heated and quenched with water – demonstrate an increase in tensile strength but a significant reduction in material plasticity. Originality/value: The presented piece of work provides a contribution for fire safety engineering giving insight into the fire behaviour of reinforcing steel under fire conditions and subjected to rapid or slow cooling. This study has shown the threats arising from thermally induced changes in steel microstructure because of high-temperature exposure. It should also be noted that structure changes may have a local character and refer to steel rebars that are exposed because of fire spalling of concrete cover.